2003
DOI: 10.3758/bf03194810
|View full text |Cite
|
Sign up to set email alerts
|

Attentional and oculomotor capture with static singletons

Abstract: Previous research has shown that in visual search static singletons have the ability to capture attention (Theeuwes, 1991a(Theeuwes, , 1992. The present study investigatedwhether these singletons also have the ability to capture the eyes. Participants had to make an eye movement and respond manually to a shape singleton while a color singleton was present. When participants searched for a unique shape while a unique color singleton was present there was strong attentional and oculomotor capture (Experiment 1).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
100
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 46 publications
9
100
1
Order By: Relevance
“…At the same time, stimulus-driven attention also seems not to apply, as previous research has shown that expected, repeated, or familiar color singletons do not capture attention in the context of a visual search task (e.g., Eimer & Kiss, 2008;Horstmann & Ansorge, 2006;Yantis & Egeth, 1999), except when participants actively search for a singleton on another dimension (Bacon & Egeth, 1994) that changes from trial to trial (Theeuwes, deVries, & Godijn, 2003). Theorists of singleton-driven attention (for an overview, see Theeuwes, 2010) also predict effects of singletons to be early, in the time range of 60-150 ms (Kim & Cave, 1999) in covert attention tasks, and on the first eye movement in overt attention tasks (Theeuwes et al, 2003). In contrast, with novel singletons attention capture occurred later, after around 400 ms, which has been shown for covert shifts (Horstmann, 2006;Horstmann & Becker, 2008), as well as for overt shifts (Horstmann & Herwig, 2015) of attention.…”
Section: Introductionmentioning
confidence: 97%
“…At the same time, stimulus-driven attention also seems not to apply, as previous research has shown that expected, repeated, or familiar color singletons do not capture attention in the context of a visual search task (e.g., Eimer & Kiss, 2008;Horstmann & Ansorge, 2006;Yantis & Egeth, 1999), except when participants actively search for a singleton on another dimension (Bacon & Egeth, 1994) that changes from trial to trial (Theeuwes, deVries, & Godijn, 2003). Theorists of singleton-driven attention (for an overview, see Theeuwes, 2010) also predict effects of singletons to be early, in the time range of 60-150 ms (Kim & Cave, 1999) in covert attention tasks, and on the first eye movement in overt attention tasks (Theeuwes et al, 2003). In contrast, with novel singletons attention capture occurred later, after around 400 ms, which has been shown for covert shifts (Horstmann, 2006;Horstmann & Becker, 2008), as well as for overt shifts (Horstmann & Herwig, 2015) of attention.…”
Section: Introductionmentioning
confidence: 97%
“…First, visual neurons in FEF signal the location of a singleton under conditions that have been shown to automatically attract attention (26,27). This selection emerges even when gaze remains fixed or shifts to a location out of the response field (20-23).…”
mentioning
confidence: 99%
“…However, in those trials in which a new object was added to the display, in about 30%-40% of the trials the eye went in the direction of the abrupt onset. Moreover, in a subsequent eye movement study, Theeuwes, de Vries, and Godijn (2003) showed that under the very same circumstances, irrelevant salient static singletons (such as a uniquely colored element) only captured attention, not the eyes. Therefore, transient singletons seem to have a different effect than static singletons, confirming the special role of abrupt onsets.…”
mentioning
confidence: 99%